Islamic Legal Modernism and Women's Emancipation in Tunisia (UINSI Samarinda, 2020)
The article aims to analyze the role of modern interpretations of Sharia on women's emancipation in Tunisia. Even though Tunisia is a Muslim country influenced by the Maliki school of thought, its social, cultural, and political conditions are conducive to women's emancipation efforts. This condition was created partly by the government's efforts to adopt Sharia's modern interpretation in Tunisia. Efforts to modernize Islamic law through state law have been going on for a long time and are consistent. Islamic legal modernism is evidenced by the Constitution, which guarantees women's equal rights, manifested in state law and policies. A case in point is family law in Tunisia that prohibits the practice of polygyny, gives equal share of the inheritance, and punishes perpetrators of domestic and sexual violence against women. Modern interpretations of Sharia have resulted in Islamic law that is more gender-friendly and maximizes women's potential in Tunisia's public sector. As a result, women's political participation in Tunisia is very high: they occupy many Parliament seats and high government bureaucracy positions. The condition of equality of women in Tunisia is far different from that of its compatriots in the middle east and north African countries, which are still influenced by conservative Islamic law interpretations.Keywords: Islamic legal modernism, women's Emancipation, polygyny prohibition, sexual harassment